Análise espacial e temporal dos fatores de erosão hídrica em latossolo vermelho-amarelo sob cultivo de pastagem e eucalipto - Quinto, Vagner Mauri (2013)
The study aimed to estimate soil loss by middle of USLE in a farming area with pasture and eucalyptus of three years of age, implanted under the pasture in area declivosa in the Southern State of ES. To estimate soil loss in the study area was made a regular mesh of 33 x 33m in a area of 10,02 ha getting 94 points of sample collection. Thematic maps were elaborated of rainfall erosivity (R) for the entire State of ES in a ten year period (1999 to 2008) relative for the cultivation of pasture and three years (2009 to 2011) relative for the cultivation of eucalyptus. Were also elaborated thematic maps of soil erodibility (K) for the study area. The thematic map of the LS factor for the study area was obtained by through of combination of steepness factor and length ramp between each sample point. The factors of USLE C and P were obtained by querying literary. The occurrence likelihood of erosivity above the third quartile for the State of ES was calculated by middle of the kriging technique indicative. A descriptive analysis was performed to determine the measurements of position and dispersion data and the normality of the data were analyzed using the Kolmogorov-Smirnov test at level in 5% probability and the results related to two period of cultivation, when necessary were compared by the test Students t test at level in 5%. All granulometric fractions and content organic study matter of soil presented spatial dependence, indicating the variability of the same within the study area. In 42,7% of the study area, increased the content of organic matter content during the cultivation period of eucalyptus when compared with the pasture, however, the content showed no significant difference (p <0.05) for the two cultures. The Center-South region of the state of ES showed the values highest annual erosivity during cultivation of the two species. However, the values of erosivity in the study area were of 8.227,2 and 8.043,2 MJ mm ha-1 h-1 for the period of pasture and of eucalyptus, respectively. The K factor showed the same pattern of spatial distribution for the study area during the cultivation of two species, being the highest values obtained in the Northwest and Southwest regions. The values of soil loss ranged from 0.0 to 14.5 t ha-1 year-1 during the period cultivated of pasture and 0.0 to 3.5 t ha-1 year-1 during the period cultivated of Eucalyptus. Soil loss in the cultivation of pasture was of 74 the 77% higher than that obtained in the cultivation of eucalyptus, being average loss of 75.4%. Some municipalities presented of 91-100% of probability of occurrence of rainfall erosivity above the third quartile, being the values most critical in the months between October and April, therefore, these municipalities need to adopt conservation practices to preserve soil. The clay and organic matter presented correlated negative with PAP, DAP and AB. Thus, eucalyptus can be used for the recovery and/or regeneration of grazing areas degraded or degradation process